Characterization of fermented foods: bone health - Tamang, Jyoti Prakash; Agahi, Fojan; Yilmaz, Birsen; Künili, İbrahim Ender; Mardon, Julie; Bulmus-Tuccar, Tuğçe; Torbica, Aleksandra; Nikolovska Nedelkoska, Daniela; Kütt, Mary-Liis; Malagón-Rojas, Jeadran; Parada, Mayra Alejandra; Mayo, Baltasar; et al. (Frontiers in Nutrition, 2025)
Fermented foods are increasingly recognized for their potential benefits in supporting bone health, attributed to their rich content of bioactive compounds including vitamins K and B, polyphenols, peptides, and fermentation-modified phytates. This review examines how these components, enhanced in bioavailability through fermentation, may modulate bone metabolism via multiple mechanisms: improving mineral absorption, reducing inflammation, regulating oxidative stress, and influencing osteoblast and osteoclast activity. Special attention is given to the gut-bone axis, where fermented foods interact with gut microbiota to produce metabolites such as short-chain fatty acids and immunomodulatory compounds that may further support skeletal health. While preclinical and population-level studies show promising associations, clinical evidence remains limited and heterogeneous. Future research should focus on human trials, strain-specific effects, and long-term outcomes to fully establish the role of fermented foods in osteoporosis prevention and bone health maintenance.